A Short Guide to Orbifold Deconstruction - Bantay, P. (Symmetry, Integrability and Geometry: Methods and Applications, 2019)
We study the problem of orbifold deconstruction, i.e., the process of recognizing, using only readily available information, whether a given conformal model can be realized as an orbifold, and the identification of the twist group and the original conformal model.